Effect of Drying Temperature on Sensory Quality, Flavor Components, and Bioactivity of Lichuan Black Tea Processed by Echa No. 10 - Dan Su; Junyu Zhu; Yuchuan Li; Muxue Qin; Zhendong Lei; Jingtao Zhou; Zhi Yu; Yuqiong Chen; De Zhang; Dejiang Ni (Molecules)
Lichuan black tea (LBT) is a well-known congou black tea in China, but there is relatively little research on its processing technology. Echa No. 10 is the main tea tree variety for producing LBT. This study investigated the sensory quality, flavor components, and bioactivity of Echa No. 10 Lichuan black tea (LBT) at different drying temperatures (70, 80, 90, 100, 110, 120, and 130 °C). During 80–120 °C, increasing the drying temperature enabled a higher sweet aroma concentration and enhanced the sweetness in the taste, in contrast to reducing the floral, fruity, and sweet aromas, and increasing the bitterness and astringency, at >120 °C. Additionally, with an increasing drying temperature, the contents of tea polyphenols and total catechins significantly decreased, with the theaflavins decreasing first and then increasing, and the alcohols, aldehydes, esters, and hydrocarbons increasing first and then decreasing. Meanwhile, compounds (including linalool, (Z)-linalool oxide (furanoid), (E)-linalool oxide (furanoid), cis-β-Ocimene, and methyl salicylate) contribute more to the floral and fruity aromas at <110 °C. Furthermore, low-temperature drying favors the antioxidant and inhibitory effects of the α-amylase, α-glucosidase, and glucose absorption activity. Both the tea quality and bioactivity results revealed 80–110 °C as the optimal drying temperature range for LBT.